FastSOA - Cohen, Frank (San Francisco, CA : Morgan Kaufmann, 2007)
Without the right controls to govern SOA development, the right set of tools to build SOA, and the right support of exciting new protocols and patterns, your SOA efforts can result in software that delivers only 1.5 transactions per second (TPS) on expensive modern servers. This is a disaster enterprises, organizations, or institutions avoid by using Frank Cohen's FastSOA patterns, test methodology, and architecture. In FastSOA you will learn how to apply native XML technology to SOA for: * Data mediation using mid-tier data and service caching to handle the explosion of new schemas and new devices in an ever changing environment * Data aggregation in the SOA middle-tier for off-line browsing, service acceleration through mid-tier caching and transformation, and bandwidth-needs reduction * Increased service and application scalability and performance * Successful evaluations of application server, XML parser, relational and native XML database, Enterprise Service Bus, Business Integration server, workflow server, and Web Service tools for performance, scalability, and developer productivity * Improved service governance through XML persistence in SOA registries and repositories * Composite data services (CDS) to provide maximum reuse of software components and data, accelerate performance, and reduce development time and maintenance in your SOA About the author Frank Cohen is the "go to" guy when enterprises need to build, test, and solve performance and scalability problems in complex interoperating information systems. Frank's articles appear on IBM developerWorks, and he is author of Java Testing and Design: From Unit Tests to Automated Web Tests. He is the principal maintainer of the popular TestMaker open-source test utility and framework, and Director of Solutions Engineering at Raining Data, publisher of the TigerLogic XQuery engine and native XML database. About the Author: Frank Cohen is the "go to" guy when enterprises need to build, test, and solve performance and scalability problems in complex interoperating information systems. Frank's articles appear on IBM developerWorks, and he is author of Java Testing and Design: From Unit Tests to Automated Web Tests. He is the principal maintainer of the popular TestMaker open-source test utility and framework, and Director of Solutions Engineering at Raining Data, publisher of the TigerLogic XQuery engine and native XML database. In FastSOA you will learn how to apply native XML technology to SOA for: * Data mediation using mid-tier data and service caching to handle the explosion of new schemas and new devices in an ever changing environment * Data aggregation in the SOA middle-tier for off-line browsing, service acceleration through mid-tier caching and transformation, and bandwidth-needs reduction * Increased service and application scalability and performance * Successful evaluations of application server, XML parser, relational and native XML database, Enterprise Service Bus, Business Integration server, workflow server, and Web Service tools for performance, scalability, and developer productivity * Improved service governance through XML persistence in SOA registries and repositories * Composite data services (CDS) to provide maximum reuse of software components and data, accelerate performance, and reduce development time and maintenance in your SOA.
The problem with service-oriented architecture -- Managing the XML explosion -- Understanding SOA patterns -- Identifying and avoiding SOA performance problems -- Solve performance problems with FastSOA patterns -- The PushToTest method to identify SOA scalability and performance metrics -- Learning XML-Centric Technology for SOA -- Getting SOA-ready.
Includes index.
Includes bibliographical references and index.
Keywords: XML (Document markup language); Computer architecture; Electronic books